The status of the German language in Poland - Mihułka, Krystyna (Glottodidactica, 2020)
The German language in Poland has a very long tradition dating back to the 18th century. Over the centuries, under the influence of historical, political, economic and social factors, the image of Germany and Germans in Poland as well as the attitude of Poles towards the German language have been subject to continual evolution. The aim of this article is to discuss the position of the German language in Poland, mainly in the 21st century. Particular attention is paid to the discussion of the importance of this language in the Polish educational system in the past two decades, and the changing number of people learning, predominantly in primary and secondary education. Moreover, the reasons for the relatively high level of dislike of the German language among Poles (including learners of German) are presented and analysed. The discussion of the current status of German in our country is preceded by a brief historical outline showing the significance of the German language in Poland as well as the attitude of Poles towards this language over the centuries, beginning with the Old-Polish period.